Navigating between adaptation and transformation: How intermediaries support businesses in sustainability transitions. (10th February 2021) - Kundurpi, Aravind; Westman, Linda; Luederitz, Christopher; Burch, Sarah; Mercado, Alexander
Abstract: Small and medium sized enterprises (SMEs) often require external support to make progress on sustainability and contribute to both environmental integrity and social well-being. Previous research has highlighted the important role of local governments and business networks as intermediaries in facilitating sustainability-action in SMEs and the pursuit of sustainability transitions in society. Missing, however, is a clear understanding of how other forms of organizations help SMEs perform sustainability-oriented actions and how various intermediaries can collectively support businesses as they contribute to social and environmental well-being. The objective of this study is to investigate the role of organizations acting as intermediaries in supporting SMEs to contribute to transitions towards sustainability. We build on the results of a large- n survey and semi-structured interviews with SMEs, non-governmental organizations, and relevant units in local government in the Greater Toronto Area (GTA) Canada. Using qualitative content analysis, our results show that local government, and more specifically economic development units and sustainability units within local government, often are disengaged from encouraging SMEs to take on sustainability-oriented initiatives. Other types of intermediaries fill knowledge and resource gaps, and act as boundary spanners in an increasingly complex web of actors, actions, and sustainability driven goals. This analysis calls for a new understanding of the role of intermediaries in sustainability transitions, in particular with regards to the relationship between incumbents and niche innovators. Highlights: Intermediaries are crucial for SMEs to undertake a diverse set of sustainability actions. Intermediaries span the boundaries between incumbent actors and niche innovators. Differentiated support functions are shaped by SME needs and the core objectives of intermediaries. SMEs and intermediaries interact in ways that resemble grassroots innovation.